Bidirectional Cross-Linguistic Association of Phonological Skills and Reading Comprehension: Evidence From Hong Kong Chinese-English Bilingual Readers. (July 2019) - Deng, Qinli; Choi, William; Tong, Xiuli
This study examined the roles of first-language (L1) Chinese and second-language (L2) English phonological skills in English and Chinese reading comprehension, respectively, and their association with reading comprehension difficulties among Hong Kong Chinese-English bilingual children. We tested 258 second graders on nonverbal intelligence, working memory, phonological skills, word reading, and reading comprehension, in both Chinese and English. Structural equation modeling analyses revealed that Chinese phonological skills contributed to English reading comprehension both directly and indirectly, through the mediation of English phonological skills and English word reading. In contrast, English phonological skills contributed only indirectly to Chinese reading comprehension through L1 Chinese phonological and word reading skills. Furthermore, poor Chinese readers, poor English readers, and poor readers in both Chinese and English exhibited lower levels of lexical tone awareness than average readers, even after controlling for nonverbal intelligence, word reading, and working memory. Poor Chinese readers outperformed poor English readers and poor readers in both Chinese and English on Chinese segmental phonological awareness, and their performance was comparable to average readers. These findings suggest that both suprasegmental and segmental phonological skills are critical to the development of reading comprehension across L1 Chinese and L2 English in Hong Kong Chinese-English bilingual children.